THE RISK FACTOR OF NEUTROPENIA ON LOCALLY ADVANCED BREAST CANCER PATIENTS TREATED WITH FIRST CYCLE CYCLOPHOSPHAMIDE, DOXORUBICINE, 5- FLUOROURACIL CHEMOTHERAPY AT SANGLAH GENERAL HOSPITAL DENPASAR, BALI-INDONESIA - Keswara, M.A.; Sudarsa, I.W.; Golden, N. (BALI MEDICAL JOURNAL, 2012)
Objective: Breast cancer is the most common type of cancer found in women, in the United States breast cancer is the number one cancer in women and the second highest cause of cancer deaths after lung cancer. This study aims to determine the incidence of neutropenia and tested several clinical risk factors of neutropenia in locally advance breast cancer/LABC patients who obtain first cycle cyclophosphamide, doxorubicine, 5-fluorouracil neoadjuvant chemotherapy at Sanglah Hospital in Denpasar. Method: The study was a prospective cohort involving 62 LABC patients conducted between February to June 2012. Clinical factors such as age, chronic obstructive pulmonary disease, hypertension, nutritional status, and hemoglobin levels in patients were recorded. Neutrophil level were recorded on day 7 and 12 of first cycle neoadjuvant chemotherapy. Bivariate analysis was done to see the strengths of each risk factor for neutropenia followed by multivariate logistic regression analysis to determine the most significant risk factor for the occurrence of neutropenia. Relative risk with 95% confidence interval was recorded. The level of significance was set at value  of less than 0,05. Results: Neutropenia was found in 17 patients (27,4%). Bivariate analysis showed that age older than 60 years old, hypotensive, under nourished, and anemic are significant risk factors of neutropenia. However, in multivariate logistic regression age (RR 20,225; 95% CI 1,804-226,776) and nutritional status (RR 35,328; 95% CI 3,108-401,524) remained significant clinical risk factors of neutropenia. Conclusion: Neutropenia incidence was 27,4%. Patients older than 60 years old and under nourished status are the significant clinical factors causing neutropenia and can be used as a predictor to predict neutropenia.